PUNISHMENT RULES AND EXTRACURRICULAR ACTIVITIES ON THE DISCIPLINE AND CHARACTER BUILDING OF STUDENTS - Putra Mahendra Gunawan Nasution; Wandana Simatupang; Muhammad Ali Napiah Lubis; Samsul Bahri Hutabarat; Amiruddin Siahaan; Inom Nasution (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This study aims to analyze the application of punishment and the implementation of extracurricular activities as an effort to discipline and shape the character of students at MTsN 2 Tapanuli Tengah. This research uses a qualitative approach with a descriptive analytical study method. The process of data collection was carried out using interview, observation, and document studies. Furthermore, the researchers carried out data reduction, data presentation, and drawing conclusions, as the stages of data analysis. Finally, the validity of the research data is recognized after going through data triangulation (methods and sources). The results of this study indicate that punishment at MTsN 2 Tapanuli Tengah, is actively carried out to create student discipline. The punishment is given in accordance with the violation of the rules carried out and the light punishment applied in the madrasa in the form of cleaning the bathroom, cleaning the madrasa yard, and doing assignments, while the severe punishment is that students are given a warning letter calling their parents to create student discipline by not repeating the violation of school rules. the same one. In addition to giving punishments, MTsN 2 Tapanuli Tengah also provides extracurricular activities to instill character and student discipline, extracurricular activities include; Tahfidzul Quran, Scouts, Intra Madrasah Student Organization (OSIM), Science Olympiad, Pencak Silat, Drum Band, Futsal, Football, and Dance. Thus, students of MTsN 2 Tapanuli Tengah are expected to be competitive, both in the academic and non-academic fields globally, and can produce high-quality and dedicated achievements.